Environmental Benefits of Community-Based Tourism Activities in Setu Babakan Betawi Cultural Village, South Jakarta - Anisa Putri Kusumaningrum; Gagih Pradini; Kumba Digdowiseiso; Fitri Agustiani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Community participation is an indicator of success in community-based tourism, a tourism destination that includes local communities in order to create collaboration and collaboration and Mutual benefits that synergize with each other. Setu Babakan Betawi Cultural Village is one of the popular destinations in Jakarta, because of its uniqueness, namely as a conservation of betawi culture in Jakarta.  community in the pariwasata activity in Setu Babakan Betawi Cultural Village using a qualitative research approach whether, in addition to using primary data researchers also use secondary data and literature studies to retrieve data.